2017
DOI: 10.1111/jvp.12392
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of enrofloxacin in healthy and Aeromonas hydrophila‐infected crucian carp (Carassius auratus gibelio)

Abstract: The comparative pharmacokinetics of enrofloxacin (ENR) and its metabolite ciprofloxacin (CIP) were investigated in healthy and Aeromonas hydrophila-infected crucian carp after a single oral (p.o.) administration at a dose of 10 mg/kg at 25 °C. The plasma concentrations of ENR and of CIP were determined by HPLC. Pharmacokinetic parameters were calculated based on mean ENR concentrations by noncompartmental modeling. In healthy fish, the elimination half-life (T ), maximum plasma concentration (C ), time to peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In the present study, the AUC ratio of CIP and ENF in largemouth bass plasma was 2.37%. In crucian carp, CIP could be detected in plasma with an AUC ratio of 2.94% following oral dose (Fan, Shan, Wang, Liu, & Zheng, ). In catfish, the AUC ratio of CIP and ENF was 3.03% (Phu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the AUC ratio of CIP and ENF in largemouth bass plasma was 2.37%. In crucian carp, CIP could be detected in plasma with an AUC ratio of 2.94% following oral dose (Fan, Shan, Wang, Liu, & Zheng, ). In catfish, the AUC ratio of CIP and ENF was 3.03% (Phu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs act by preventing DNA supercoiling through the inhibition of bacterial DNA gyrase (Dimitrova, Haritova, Dinev, Moutafchieva, & Lashev, ). The pharmacokinetics of several fluoroquinolones have previously been reported in fish species, including difloxacin in gibel carp (Cao, Zhang, He, Zheng, & Yang, ), sarafloxacin in crucian carp (Fang, Zhou, & Liu, 2016b), and enrofloxacin in grass carp (Xu, Wang, Yang, & Lu, ), Nile tilapia (Teles, Branco, Del Bianchi, Pilarski, & Reyes, ), snakehead fish (Fang et al., ), and crucian carp (Fan et al., ).…”
Section: Introductionmentioning
confidence: 96%
“…And its systemic availability after parenteral dose was not available in fish. In addition, some studies showed that the pharmacokinetics of fluoroquinolones may be affected by factors, such as species specificity, health condition, age and size, water temperature, salinity, routes of drug administration, and other experimental conditions (Cao et al., ; Dimitrova et al., ; Fan et al., ; Martinez et al., ). Therefore, it is necessary to study the pharmacokinetics of orbifloxacin in other fish species and/or under other routes of administration.…”
Section: Introductionmentioning
confidence: 99%
“…Enrofloxacin serves as a last-line treatment in aquaculture, and it effectively treats the bacterial infections caused by F. columnare (6), A. hydrophila (9), and A. sobria (10). The plasma pharmacokinetics of enrofloxacin has been reported in some fish species, such as crucian carp (11,12), large yellow croaker (13), tilapia (14), snakehead fish (15), brown turbot (16), and salmonids (17). In addition to those pharmacokinetics studies, the tissue distribution of enrofloxacin has also been reported in aquaculture species, including northern snakeheads (18), rainbow trout (19,20), grass carp (21), largemouth bass (22), and pacu (23).…”
Section: Introductionmentioning
confidence: 99%